Structural analysis and dielectric relaxation mechanism of conducting polymer/volcanic basalt rock composites - Bulgurcuoglu, Ayse Evrim; Karabul, Yasar; Kilic, Mehmet; Ozdemir, Zeynep Guven; Erdonmez, Seda; Misirlioglu, Banu Sungu; Okutan, Mustafa; Icelli, Orhan (SCIENDO, 2019)
In this work, polypyrrole and polythiophene conducting polymers (CPs) have been synthesized and doped with volcanic basalt rock (VBR) in order to improve their dielectric properties for technological applications. The structure and morphology of the composites with different VBR doping concentrations were characterized by FT-IR and SEM analyses. The best charge storage ability was achieved for maximum VBR doping concentration (50.0 wt.%) for both CPs. Dielectric relaxation types of the composites were determined as non-Debye type due to non-zero absorption coefficient and observation of semicircles whose centers were below Z ' axis at the Nyquist plots. It was also ascertained that VBR doping makes the molecular orientation easier than for non-doped samples and reduced energy requirement of molecular orientation. In addition, AC conductivity was totally masked by DC conductivity for all samples at low frequency.
Keywords: composite materials; polypyrrole; polythiophene; volcanic basalt rock; dielectric spectroscopy; ABSORPTION PROPERTIES; SHIELDING PROPERTIES; IMPEDANCE PROPERTIES; AC CONDUCTIVITY; NANOTUBES; NANOCOMPOSITE; GRAPHITE; POLYMERS; Materials Science